Muscle Oxygen Delivery in the Forearm and in the Vastus Lateralis Muscles in Response to Resistance Exercise: A Comparison Between Nepalese Porters and Italian Trekkers - Verratti, Vittore; Bondi, Danilo; Mulliri, Gabriele; Ghiani, Giovanna; Crisafulli, Antonio; Pietrangelo, Tiziana; Marinozzi, Maria E.; Cerretelli, Paolo (Frontiers in Physiology, 2020)
Altitude ascending represents an intriguing experimental model reproducing physiological and pathophysiological conditions sharing hypoxemia as the denominator. The aim of the present study was to investigate fractional oxygen extraction and blood dynamics in response to hypobaric hypoxia and to acute resistance exercises, taking into account several factors including different ethnic origin and muscle groups. As part of the “Kanchenjunga Exploration & Physiology” project, 6 Italian trekkers and 6 Nepalese porters took part in a high-altitude trek in the Himalayas. The measurements were carried out at low (1450 m) and high altitude (4780 m). Near infrared spectroscopy (NIRS)-derived parameters, i.e. Tot-Hb and tissue saturation index (TSI), were gathered at rest and after bouts of 3-minutes resistive exercise, both in the quadriceps and in the forearm muscles. TSI decreased with altitude, particularly in forearm muscles (from 66.9% to 57.3%), whereas the decrement was less in the quadriceps (from 62.5% to 57.2%); Nepalese porters were characterized by greater values in thigh TSI than Italian trekkers. Tot-Hb was increased after exercise. At altitude, such increase appeared to be higher in the quadriceps. This effect might be a consequence of the long-term adaptive memory due to the frequent exposures to altitude. Although speculative, we suggest a long-term adaptation of the Nepalese porters due to improved oxygenation of muscles frequently undergoing hypoxic exercise. Muscle structure, individual factors, and altitude exposure time should be taken into account to move on the knowledge of oxygen delivery and utilization at altitude.